STUDENTS' PERCEPTION OF PHYSICAL EDUCATION COURSES AND ITS RELATIONSHIP WITH THEIR PARTICIPATION IN SPORT ACTIVITIES - Mohsen Ghofrani; Masoumeh Golsanamlou (Sport Scientific And Practical Aspects, 2025)
This study examined students' attitudes towards PE lessons and their perceptions of Physical Education lessons. The methodology of this study was a quantitative research. The population of this study included all students of Sistan & Baluchestan University. Out of 18750 students with using Morgan’s (1970) sample size table, 380 students (150 boys and 230 girls were selected as two sample groups and were introduced to the questionnaire used in this study. The questionnaire has 42 items by a four point Likert-type scale ranging from (1) strongly disagree to (4) strongly agree in six components: Students' attitudes towards PE, their perceptions of PE lessons, perceived athletic competence, perceived benefits of exercise, intention to exercise, and current exercise behavior. SPSS 15 was used to produce mean; standard deviations; Pearson product moment correlation (r); T-test; Bonferroni Post Hoc test; and Analysis of Variance. The results showed that students in were having positive perception (X=34.68; SD=4.03) and favorable attitudes towards Physical Education lessons (X=31.88; SD=3.49). Almost, in all variables boys adopted more favorable attitudes than girls. Boys spent more of their leisure time in sports activities (Never or Once 62%) than girls (Never or Once 74%). Younger students adopted more favorable attitudes than oldest (F (3,377) = 3.536, P<.05). There was relatively, high positive correlation between six variables. According to the findings above, suggestions were given to sport system and future research.